Determinants and Dynamics of SARS-CoV-2 Infection in a Diverse Population: 6-Month Evaluation of a Prospective Cohort Study. (13th August 2021) - Horton, Daniel B; Barrett, Emily S; Roy, Jason; Gennaro, Maria Laura; Andrews, Tracy; Greenberg, Patricia; Bruiners, Natalie; Datta, Pratik; Ukey, Rahul; Velusamy, Senthil K; Fine, Daniel; Honnen, William J; et al.
Abstract: Background: We studied risk factors, antibodies, and symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a diverse, ambulatory population. Methods: A prospective cohort (n = 831) previously undiagnosed with SARS-CoV-2 infection underwent serial testing (SARS-CoV-2 polymerase chain reaction, immunoglobulin G [IgG]) for 6 months. Results: Ninety-three participants (11.2%) tested SARS-CoV-2-positive: 14 (15.1%) asymptomatic, 24 (25.8%) severely symptomatic. Healthcare workers (n = 548) were more likely to become infected (14.2% vs 5.3%; adjusted odds ratio, 2.1; 95% confidence interval, 1.4–3.3) and severely symptomatic (29.5% vs 6.7%). IgG antibodies were detected after 79% of asymptomatic infections, 89% with mild-moderate symptoms, and 96% with severe symptoms. IgG trajectories after asymptomatic infections (slow increases) differed from symptomatic infections (early peaks within 2 months). Most participants (92%) had persistent IgG responses (median 171 days). In multivariable models, IgG titers were positively associated with symptom severity, certain comorbidities, and hospital work. Dyspnea and neurologic changes (including altered smell/taste) lasted ≥ 120 days in ≥ 10% of affected participants. Prolonged symptoms (frequently more severe) corresponded to higher antibody levels. Conclusions: In a prospective, ethnically diverse cohort, symptom severity correlated with the magnitude and trajectory of IgG production. Symptoms frequently persisted for many months after infection. Clinical Trials Registration. NCT04336215. Abstract : In a diverse, ambulatory cohort (548 healthcare workers; 283 nonhealthcare workers), 11.2% tested positive for SARS-CoV-2 over 6-month follow-up. COVID-19 symptom severity correlated with magnitude and trajectory of IgG production. Symptoms lasting ≥ 30 days afflicted one-third of infected participants.